Settlement dynamics on the banks of the upper Tigris, Iraq: The Mosul dam reservoir survey (1980) - Sconzo, P; Simi, F (Ubiquity Press, Ltd., 2020)
The paper describes a dataset of archaeological sites and villages now partially covered by the water of the Mosul Dam Reservoir. For the first time the dataset offers digitized information on c.150 archaeological sites detected during a survey carried out by the Iraqi State Organization for Antiquities and Heritage in the 1980s. Knowledge of the map of these sites will have a substantial impact on interpretation of Tigridian settlement dynamics.